YOGA, MEDITATION, AND PERFORMANCE PRACTICE: ENHANCING CREATIVITY, PRESENCE, AND WELL-BEING - Singh, Surendra Pal; Kalyani, Lohans Kumar; Singh, Manju; Verma, Anuj Kumar; Yadav, Pradeep Kumar; Rani, Bindu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
There has been increasing research on the application of yoga and meditation to the composition of performing arts as one of the comprehensive approaches to creativity, stage performance, and well-being of the performers. Exposing the works of art to intense physical exercises, emotional outbursts, and excessive psychological stress, tend to affect the performance, as well as their health in long-term. This paper discusses yoga and meditation as mind-body practices, which assist an artist to develop and perform sustainably. The study will be based on interdisciplinary literature in the performing arts, psychology and mindfulness studies to give the contribution of meditative practices to increased physical awareness, cognitive concentration, emotional control and creative engagement. The paper proceeds to discuss the history and philosophy of yoga and meditation and how it can be applied to training in art. It also reiterates the significance of such practices as asana (poses), pranayama (breath control) and meditation to enhance alignment in the body, breathing performance and clarity of mind in the performers. These practices are particularly applicable in arts such as dance, music, theatre where the performers are required to rely on the capability to make movements of their body in coordination, expressive interpretation and focus. The mindfulness-based interventions also help reduce performance anxiety, and emotional resilience, such that the performers will be calm and in the here and now when preparing their performance and to perform on stage. Besides this, the paper also constructs a Mindfulness-Based Performance Framework which integrates yoga, breath control, meditation and creative performance practices into a model training. The framework is concerned with interdependent relationship between the physical training, mind concentration and art. These factors may be incorporated into the education of performing arts and rehearsal techniques in order to allow the artists to gain a deeper understanding of themselves, greater creativity process and confidence in the stage. The findings suggest that yoga and meditation are valuable assets of promoting the overall development of art and promoting the well-being of the involved performer.